DIAGNOSTIC ASSESSMENT ON THE INDEPENDENT LEARNING CURRICULUM IN PAI LEARNING - Silvia, Atik; Quraisy, Sherly; Maimun; Inayati, Mahfida; Arifin, Moh Syamsul (INTIHA: Islamic Education Journal, 2024)
This study aims to evaluate the effectiveness of diagnostic assessment in identifying students' initial needs, as well as its influence on the planning and implementation of learning which is more responsive and by student characteristics. The research method used is field research with a descriptive approach. Primary data was obtained through observation results while field data was obtained through learning assessments. Secondary data were collected from relevant literature studies and journal articles supporting this study. The study's findings showed that diagnostic assessment at SDN Pamaroh 1 was proven to identify students' learning needs more specifically. Thus, teachers were more easily adjust their teaching methods. It not only increases students' understanding of PAI material but also increases their motivation and involvement during the learning process. Based on these findings, it is recommended that more intensive and continuous training should be provided for teachers regarding diagnostic assessment techniques and their use in the independent curriculum. In addition, further research is necessitated to explore effective ways to overcome the obstacles faced and to measure the long-term impact of diagnostic assessment on student learning outcomes.